MODEL PEMBELAJARAN BERBASIS WEB APLIKASI DENGAN MENGGUNAKAN PENDEKATAN SMART CLASS PADA MATA KULIAH SISTEM KELISTRIKAN KAPAL DI POLITEKNIK PELAYARAN SUMATERA BARAT (Universitas PGRI Sumatera Barat, 2022)
Based on the preliminary research conducted by the researcher, several things were found that became obstacles in the learning process, especially the media/platform used during virtual learning at Politeknik Pelayaran Sumatera Barat. Therefore, the researcher developed a learning management model product based on a web application. It is hoped that it can increase motivation and help the difficulties of cadets who have below average competence to catch up with their friends who have better competence than them. In addition, through this learning management model, it is expected to create an innovative learning management model that is integrated with technology. The ship electrical system learning model was developed from a factual model and adapted to the needs analysis of cadets and lecturers during online learning, then developed to increase cadets' motivation to learn while online. The feasibility level of this application web-based learning model can be seen from the results of the questionnaire given to users, namely lecturers and cadets which show that 88.5% of the ship's electrical system learning management model is feasible to be implemented at Politeknik Pelayaran Sumatera Barat. Learning activities in the ship's electrical system course, this is evidenced by the results of the questionnaire, the cadets’ learning motivation increased by 89%